2001
DOI: 10.1111/j.1835-2561.2002.tb00389.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining Ethical Investment and its Demography in Australia

Abstract: While ethical investment is relatively new in Australia, it is a well defined phenomenon in the United States and United Kingdom, subject to variations in interpretation in its practical implementation. Characteristics of ethical investment decision‐making suggest ethical investors may be demographically different from “ordinary” investors. This descriptive paper reports on a survey of equity investors in Australia, comparing the average investor and an ethical investor. The main findings are that there is evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 19 publications
2
23
3
Order By: Relevance
“…These individuals are neither cranks nor saints: they are commonly middle-income professionals mixing ethical investments with not so ethical ones. Tippet and Leung's (2001) study of 300 Australian Shareholders' Association members, and members of the equityinvesting Australian public, indicated that while the principles of applying ethical criteria to the selection of investment stocks appears reasonable, the practical application of these can be difficult. A major aspect is the relative importance and subsequent actions of the investor when a company departs from ethical criteria.…”
Section: Ethical Investorsmentioning
confidence: 98%
“…These individuals are neither cranks nor saints: they are commonly middle-income professionals mixing ethical investments with not so ethical ones. Tippet and Leung's (2001) study of 300 Australian Shareholders' Association members, and members of the equityinvesting Australian public, indicated that while the principles of applying ethical criteria to the selection of investment stocks appears reasonable, the practical application of these can be difficult. A major aspect is the relative importance and subsequent actions of the investor when a company departs from ethical criteria.…”
Section: Ethical Investorsmentioning
confidence: 98%
“…In the 18 th century, the Religious Society of Friends, better known as the Quakers, refused to profit from war or slave-running activities (Kinder, Lydenberg & Domini 1993;Hutton, D'Antonio & Johnson 1998;& Schwartz 2003). Indeed Quaker business proprietors (such as Rowntree and Cadbury) were leaders in humanitarian initiatives and ethical business during this period (Tippett & Leung 2001). In the 1920s, the Methodists began investing in the share market, when they declared that it was no longer akin to gambling.…”
Section: The Development Of Srimentioning
confidence: 99%
“…However as SRI is influenced by individual values and beliefs, it is difficult to describe the term definitively (Tippett & Leung 2001). This is complicated by the significant variation across countries in terms of operationalisation of SRI and the different levels of take-up (Arjalies 2010;Williams 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the interest in SRI by academics and participants in the marketplace, the understanding of the motives, psychology, and decision-making of individual socially responsible investors 1 is still incomplete and still largely limited to descriptive accounts (Anand and Cowton, 1992;Cullis et al, 1992;Lewis and Mackenzie, 2000a, b;Mackenzie and Lewis, 1999;Rosen et al, 1991) or studies comparing the characteristics of investors who invest in SRI and those that do not (Lewis, 2001;McLachlan and Gardner, 2004;Tippet and Leung, 2001). Not only is there only a scantly developed theoretical basis for understanding SRI, but there is also little knowledge about the individual and contextual variables that predict the investor's decision to consider social criteria in their portfolio selection.…”
mentioning
confidence: 99%